2021
DOI: 10.21037/tcr-20-2969
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, YWHAE, SP1 and MSRA as biomarkers in endometrial cancer

Abstract: Background: We demonstrated that drinking hydrogen-rich water (HRW) inhibits endometrial tumor growth in our previous work. This research is to identify differentially expressed proteins (DEPs) between HRW and purified water groups in a xenograft mouse model of endometrial cancer (EC).Methods: Samples were analyzed using tandem mass tags (TMTs) coupled with liquid chromatographytandem mass spectrometry (LC-MS/MS). DEPs were identified using bioinformatics to determine potential molecular functions and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In the rst part of the study, we illustrated that YWHAE regulated exosome sorting of miR-451a into exosomes. YWHAE promotes cancer progression and can be a potential therapeutic target in multiple cancer types such as breast cancer [19], endometrial cancer [29], and Prostate cancer [30].In this study, we demonstrated that YWHAE transported miR-451a from tumor cells to exosomes. The complex of YWHAE and miR-451a were packed into exosomes leading to the reduction of ESCC cells miR-451a.…”
Section: Discussionmentioning
confidence: 55%
“…In the rst part of the study, we illustrated that YWHAE regulated exosome sorting of miR-451a into exosomes. YWHAE promotes cancer progression and can be a potential therapeutic target in multiple cancer types such as breast cancer [19], endometrial cancer [29], and Prostate cancer [30].In this study, we demonstrated that YWHAE transported miR-451a from tumor cells to exosomes. The complex of YWHAE and miR-451a were packed into exosomes leading to the reduction of ESCC cells miR-451a.…”
Section: Discussionmentioning
confidence: 55%
“…7 ). Several earlier studies have already confirmed that Sp1 and Sp1 -regulated genes were related to the development of EC [ 27 , 28 ]. Thus, our results indicated that ZBTB4 is a potential target of miR-576-5p and their interaction affects EC cell growth and metastasis.…”
Section: Resultsmentioning
confidence: 82%
“…With the deepening of the understanding of endometrial cancer, clinicians will consider and choose drugs according to different molecular subtypes of endometrial cancer, and MSI-H/dMMR is a very important molecular state. There are several ongoing clinical studies which monoclonal antibodies have been evaluated for the treatment of tumors expressing high levels of immune checkpoint-associated proteins ( 21 - 24 ). The results also indicate that advanced or metastatic stages could benefit from targeted adjuvant therapies based on molecular alterations, particularly considering advanced MSI-H/dMMR ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%